2005
DOI: 10.1007/s00280-004-0914-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of P-glycoprotein transport function and reversion of MDR1 multidrug resistance by cnidiadin

Abstract: Cnidiadin is a cytotoxic agent capable in vitro of competitively inhibiting the binding and efflux of drug by Pgp and of enhancing the cell toxicity of vinca alkaloids in two cell lines (MDCK-MDR1 and mutant human carcinoma KB/VCR) overexpressing Pgp. This suggests that diet or traditional preparation containing cnidiadin may contribute to the reversal of MDR1 multidrug resistance and may affect the bioavailability of Pgp substrates orally administered. However, due to its cell toxicity, clinical interest in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…Previous study shown that six natural coumarins (umbelliferone, esculin, esculetin, cnidiadin, angelicin and psoralen), only cnidiadin was capable of significantly accumulating rhodamin-123 and inhibit ABCB1 photolabeling in MDR1-transfected MadinDarby canine kidney (MDCK-MDR1) cells (Barthomeuf et al, 2005). This study indicate that the results of psoralen decrease ABCB1 expression and capability inhibit ABCB1 pumping activity may have cellular specific correlation.…”
Section: Discussionmentioning
confidence: 60%
“…Previous study shown that six natural coumarins (umbelliferone, esculin, esculetin, cnidiadin, angelicin and psoralen), only cnidiadin was capable of significantly accumulating rhodamin-123 and inhibit ABCB1 photolabeling in MDR1-transfected MadinDarby canine kidney (MDCK-MDR1) cells (Barthomeuf et al, 2005). This study indicate that the results of psoralen decrease ABCB1 expression and capability inhibit ABCB1 pumping activity may have cellular specific correlation.…”
Section: Discussionmentioning
confidence: 60%
“…cyclosporine [9], valspodar (PSC 833) [10], Pyronaridine [11], and natural and synthetic polymers [12]. Numerous plant-derived dietary compounds, for instance cnidiadin and schizandrins, could also modulate P-gp transport [13,14]. However, the results of clinical trials with these compounds have been disappointing because of side effects and/or weak potency.…”
Section: Introductionmentioning
confidence: 99%
“…However, when co-treatment with cnidiadin (10 mM)/VCR on the KB/VCR cells, the cells resulted from long-term exposure of the parental sensitive KB human oral epidermis carcinoma cell line to VCR. No cell toxicity was detected after exposure to cnidiadin and cnidiadin sensitized KB/VCR cells 103 . In another study, bioguided fractionation from the roots of Citrus sinensis (Rutaceae) led to the isolation and identification of five coumarins, namely, clausarin, suberosin, poncitrin, xanthyletin and thamnosmonin 104 .…”
Section: Coumarinsmentioning
confidence: 90%